2000
DOI: 10.1038/sj.ijo.0801168
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polymorphisms of the human β2-adrenoceptor gene on obesity in a French population

Abstract: OBJECTIVE: To investigate the impact of two common polymorphisms in the human b b 2 -adrenoceptor gene (Gly16Arg and Gln27Glu substitutions) on obesity and anthropometric measurements as well as blood variables in a large sample of a French population. DESIGN AND SUBJECTS: Within the framework of the WHO-MONICA project, a population study composed of 1195 subjects aged 35 ± 64 y was randomly sampled from the electoral rolls of the Urban Community of Lille, in northern France. Subjects without any medical treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 27 publications
7
57
1
2
Order By: Relevance
“…The present case-control study, quantitative trait analysis and meta-analysis did not provide evidence of an impact of the variant on obesity, which is consistent with previously performed case-control studies [2,[4][5][6][7][8][9]. Previous studies have suggested sex differences [16].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present case-control study, quantitative trait analysis and meta-analysis did not provide evidence of an impact of the variant on obesity, which is consistent with previously performed case-control studies [2,[4][5][6][7][8][9]. Previous studies have suggested sex differences [16].…”
Section: Discussionsupporting
confidence: 92%
“…The Arg allele frequency of the ADRB2 Arg16Gly variant (38%) was similar to previously identified allele frequencies [2,4,5]. The present case-control study, quantitative trait analysis and meta-analysis did not provide evidence of an impact of the variant on obesity, which is consistent with previously performed case-control studies [2,[4][5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lipolysis of triglyceride stores is regulated by catecholamines and sympathomimetic stimuli via beta-adrenergic receptors, resulting in activation of the cyclic AMP/protein kinase A (cAMP/PKA) cascade, phosphorylation and translocation of hormone-sensitive lipase (HSL) from the cytoplasm to the lipid droplet. Various polymorphisms in the beta2-and beta3-adrenergic receptors have been reported in relationship with obesity (36)(37)(38)(39). The HSL knockout mouse exhibits male sterility and adipocyte hypertrophy but not obesity, as well as normal basal lipolysis but blunted response to catecholamines (40).…”
Section: Regulation Of Energy Balancementioning
confidence: 99%